Pneumatosis Intestinalis Associated with Massive Intraperitoneal Free Air Mimicking Intestinal Perforation: Case Report (Annals of Medical Research, 2021)
None
Keywords: Pneumatosis Intestinalis; Intestinal Perforation; Air Cyst.